The small cardioactive peptides A and B of Aplysia are derived from a common precursor molecule. - Mahon, A C (1985)
We have identified cells in the central nervous system of the marine mollusc Aplysia that react with antibody raised against the small cardioactive peptide B (SCPB). Antisera to this neuropeptide stained a subset of central neurons that include the large identified buccal neurons, B1 and B2. The distribution of SCP-containing neurons was used in a strategy to isolate a cDNA clone encoding the precursor protein for the peptide. RNA from neurons B1 and B2 and from cells that did not stain with SCPB antisera was used to direct the synthesis of radiolabeled cDNA probes. A cDNA clone complimentary to mRNA specifically expressed in the B1 and B2 cells was isolated by differentially screening a buccal cDNA library with these probes. The cloned cDNA segment is 1394 nucleotides in length and contains a 408-base-pair open reading frame. The predicted precursor protein is composed of 136 amino acids and has a characteristic hydrophobic leader sequence. The sizes of the precursor protein with and without this leader sequence agree with in vivo and in vitro labeling studies. The amino acid sequences for SCPB and a related peptide, SCPA, are present and are flanked by known proteolytic processing sites.